A Comparative Study on Religiosity and Spirituality Among Male and Female Psychologists - Fathima Fiba E.K; Sana Fathima (Emerging Trends in Languages, 2026)
The current study looked at the differences in religiosity and spirituality between male and female psychologists. We selected 60 participants through a convenient sampling method, which included 30 male and 30 female psychologists. The study focused on understanding how gender may influence religious beliefs and spiritual orientation within a professional psychological context. To assess these constructs, standardized tools were employed: Glock’s Religiosity Measure to evaluate levels of religiosity, and Delaney’s Scale for Spirituality to measure spiritual experiences and perspectives. These instruments provided a structured approach to quantify abstract constructs such as faith, beliefs, practices, and personal spiritual awareness. The data collected were analyzed using an independent samples t-test to determine whether there were statistically significant differences between male and female psychologists in terms of religiosity and spirituality. The findings showed that there are important differences between the two groups. This suggests that gender influences both religiosity and spirituality among psychologists. These results highlight the importance of considering gender-based perspectives when exploring psychological variables related to belief systems and inner experiences. The study contributes to the growing body of literature that integrates psychological practice with personal belief frameworks, emphasizing that psychologists themselves are influenced by sociocultural and personal factors such as religion and spirituality.
Keywords: Religiosity; belief systems; delaney’s spirituality scale; gender differences; glock’s religiosity measure; spirituality; t-test